2004
DOI: 10.1007/s10750-004-6418-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, nitrogen, and sulfur isotope changes and hydro-geological processes in a saline lake chain

Abstract: The ionic concentrations,conductivity and pH of water in the Lake Chany complex in West Siberian Russia change from the mouth to the interior of the lake. This difference is indicative of marked evaporation of lake water from the closed water body system in the dry climate of Western Siberia. The carbon isotope composition of particulate organic matter (POM, composed mainly of phytoplankton) clearly changes, along with the pH of the water, reflecting the concentration of dissolved CO 2 . Carbon and nitrogen is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…EC at Stations 1-4 had low values ranging from 0.11 to 0.14 mS m )1 . The difference between Station 5 and Stations 1-4 reflects the evaporation of water and an accumulation of salt (Doi et al, 2004). Chlorophyll a showed higher values at the low EC stations (Stations 1-4).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…EC at Stations 1-4 had low values ranging from 0.11 to 0.14 mS m )1 . The difference between Station 5 and Stations 1-4 reflects the evaporation of water and an accumulation of salt (Doi et al, 2004). Chlorophyll a showed higher values at the low EC stations (Stations 1-4).…”
Section: Resultsmentioning
confidence: 94%
“…This lake is a shallow, inland, and saline system (average depth, 2.2 m; maximum depth, 8.5 m) characteristic of the Western Siberian forest-steppe (Aladin & Plotnikov, 1993;Doi et al, 2004). Lake Chany is an enclosed water body comprised of three lakes, Bolshye Chany, Malye Chany, and Yarkul, which are connected by small channels (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Doi et al (2004Doi et al ( , 2006 demonstrated the importance of phytoplanktonic production to the zooplankton and benthic chironomid larvae in the ecosystem. The food web structure, however, has not been fully characterised, particularly in regard to the contribution of various producer groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…No permafrost underlies the Barabinsk Steppe. The lake is moderately saline, and conductivity ranges from 0.19 to 1.12 S m −1 (Doi et al 2004). The average depth of the Lake Chany complex is about 2.2 m, with a maximum depth of 8.5 m (Aladin and Plotnikov 1993).…”
Section: Introductionmentioning
confidence: 99%